Highly Regulated Service Firm To Achieve Sustainable Competitive Advantage Through Resource-Based View and Service Dominant Logic Integration – Lessons from The Practice Of PT Angkasa Pura I (Persero) - Pratama, Albertus Indra (2018)
With the rise of technology and changing customer culture and trend, in order for the highly regulated service firm to gain a sustained competitive advantage, the firm needs to be able to innovate and create better product or service offering that not contradicted with the regulation. To understand the strategy of highly regulated service firm to achieve sustained competitive advantage the internal resources and capabilities are analyzed through Resource-Based View, then examine the firm orientation and value co-creation process using Service Dominant Logic. Highly regulated service firm will be represented by Indonesian airport company which is PT Angkasa Pura I (Persero), then, the two theories are integrated in order for the firm to be able to gain the sustained competitive advantage. Based on the firm internal source of competitive advantage the strategic location and human capital are the sources of sustained competitive advantage for the airport and it allows the airport to collaboratively working with the passengers to create value.